Task Level Decrease Commitment Due to Zoom Fatigue In Nursing Faculty, Padjadjaran University - Iyus Yosep; Dimas Wibawa Sakti; Furkon Nurhakim (Eduvest - Journal of Universal Studies, 2022)
The Covid-19 pandemic that hit the world, Indonesia is no exception, has had a huge impact on various sectors, one of which is the education sector. Many activities that must be done online cause students to experience fatigue commonly called zoom fatigue and affect the task commitment level of students. The purpose of this study was to determine the relationship between Zoom fatigue and level tasks commitment on the students-level I Faculty of Nursing, University of Padjadjaran. This type of research is quantitative with a descriptive correlation design. The data collection technique used in this study is a questionnaire using google forms. The instrument used in this study is the Zoom fatigue & Fatigue Scale to measure zoom fatigue and the Task Commitment level Scale to measure task commitment levels. Data analysis conducted in this study is to use Rank spearman to test the hypothesis test. The results of data analysis conducted using the Spearman correlation technique obtained a sig value of 0.119 > 0.05 then it was concluded that there is no significant relationship between Zoom fatigue and task commitment level in Level I Students of the Faculty of Nursing, University of Padjadjaran. Researchers are further advised to identify also related to other variables that affect the level of task commitment such as punishment, reward, and praise, as well as environmental conditions.